A novel method to prevent biting through nasolabial flap: Modified oral screen. Issue 2 (March 2018) - Chaudhary, Zainab; Bodh, Ranjeet; Sharma, Pankaj; Mohanty, Sujata; Verma, Anjali
Abstract: Objective: Oral submucous fibrosis (OSMF) is a chronic, progressive precancerous condition of oral mucosa, predominantly seen in the Indian subcontinent. This technical note describes the use of oral screen prosthesis used as an adjunct to surgery to prevent relapse following surgical correction. Methods: The modified oral screen appliance was inserted in the patient's labial and buccal vestibule as oral screen. The appliance was intended to be used as an oral stent along with mouth exercises to counteract relapse of the corrected mouth opening. Results: The possibility of flap shrinkage and interference with occlusion results in surgical failure of the treatment of OSMF. Securing the flap in position using oral screen prosthesis has been tried as an adjunct to treat such cases. Conclusions: This modified approach can be performed in routine clinical practice, making the rehabilitation of such a case possible with relative ease.